ANALISIS PENGARUH MODEL-VIEW-VIEWMODEL TERHADAP KINERJA APLIKASI COMFY LEARN - Juan Kevin Raintung; Syaiful Rahman; Abdul Munir S (KHARISMA Tech, 2026)
Interactive learning applications for early childhood, such as Comfy Learn, play an important role in the digital age. However, poor technical performance can hinder their pedagogical effectiveness. This study aims to analyze and improve the performance of Comfy Learn by implementing the Model-View-ViewModel (MVVM) architecture pattern, recommended by Google for modern Android applications. A quantitative approach was used by comparing performance metrics (CPU usage, memory consumption, and janky frames) and code maintainability metrics (Source Lines of Code, Cyclomatic Complexity, Cognitive Complexity) before and after migrating to MVVM. Testing was conducted with Android Studio Profiler, Firebase Test Lab, and SonarQube under standardized procedures. Results show that MVVM implementation reduced janky frames by 46.3% (p < 0.05), lowered code complexity by 37.5%, and improved application stability. This study provides empirical evidence that MVVM not only improves technical performance but also enhances long-term maintainability of Android-based educational applications.